The Impact of IoT and Production Tracking Systems on Delivery Timeliness in the Electronics Industry in Tangerang City - Ajub Ajulian ZM; Enda Wista Sinuraya; Karnoto Karnoto; Gogor Christmass Setyawan (Westscience Press, 2026)
The rapid adoption of Industry 4.0 technologies has encouraged manufacturing companies to integrate Internet of Things (IoT) solutions and production tracking systems to improve operational performance and delivery reliability. This study aims to analyze the impact of IoT implementation and production tracking systems on delivery timeliness in the electronics industry in Tangerang City. A quantitative research approach was applied using survey data collected from 150 employees involved in production and logistics activities. Data were measured using a five-point Likert scale and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to evaluate both measurement and structural models. The results indicate that IoT implementation has a positive and significant effect on delivery timeliness by enabling real-time monitoring and faster operational coordination. Production tracking systems also show a strong positive influence by improving scheduling accuracy, workflow visibility, and decision-making processes. Furthermore, the integration of IoT and production tracking technologies contributes to better supply chain responsiveness and reduced delivery delays. These findings highlight the strategic role of digital monitoring systems in enhancing manufacturing performance and meeting customer delivery expectations. This study provides empirical insights for practitioners and contributes to the growing literature on smart manufacturing and technology-driven operational efficiency in Indonesia’s electronics sector.